Outside and inside you - Markle, Sandra (New York : Bradbury Press, 1991)
Discusses the various parts of the body and their functions.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
4.9
K-3
Keywords: Body, Human -- Juvenile literature; Human anatomy -- Juvenile literature; Body, Human; Human anatomy; Human anatomy